APPLICATION OF CAD / CAM PILOT IN THE MANUFACTURE OF CLOTHING OF PLANT Fll - UNMSM - Rojas Lazo, Oswaldo (1999)
This paper presents a CAD / CAM system used in apparel garment, the advantages over the traditional system and the possibility of gradually implemented in the pilot plant confection of Fll - San Marcos.